2010
DOI: 10.1158/0008-5472.can-09-4100
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of BRCA1 and Lethal Prostate Cancer

Abstract: BRCA1 functions as a tumor suppressor; recent work suggests that BRCA1 may also induce cell cycle arrest to allow for DNA repair. We hypothesized that BRCA1 expression in prostate tumor tissue may be associated with prostate cancer progression through regulation of the cell cycle. We used immunohistochemistry to evaluate BRCA1 protein expression in archival tumor samples from 393 prostate cancer cases in the Physicians' Health Study. The men were followed prospectively from diagnosis to development of metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…Areas of negative and positive staining were found in the same tumor, and PML bodies were rarely visualized. This lack of PML bodies in tumor cells can explain why prostate tumors exhibit high levels of expression of E2F target genes such as EZH2 (Stanbrough et al 2006) and BRCA1 (Schayek et al 2009;Fiorentino et al 2010). Interestingly, BRCA1 was one of the genes more efficiently down-regulated in PML-senescent fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Areas of negative and positive staining were found in the same tumor, and PML bodies were rarely visualized. This lack of PML bodies in tumor cells can explain why prostate tumors exhibit high levels of expression of E2F target genes such as EZH2 (Stanbrough et al 2006) and BRCA1 (Schayek et al 2009;Fiorentino et al 2010). Interestingly, BRCA1 was one of the genes more efficiently down-regulated in PML-senescent fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas mutations in BRCA1 may influence familial prostate cancer progression, few studies have examined BRCA1 protein expression in prostate cancer tumor tissue. Fiorentino and colleagues (43) had addressed this important point and they found that human prostate tumor samples stained positive for BRCA1 had significantly higher Gleason score, PSA at diagnosis, and tumor proliferation as well as significantly worse prognosis than those with negative BRCA1 staining. Additionally, our results showing that BRCA1 loss of function is also involved in the differential response to DNA damage agents can also explain why the evolution of the disease could be favored or not by the presence of BRCA1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of agreement were seen for ER-β categorical scores (; κ = 0.80-0.86), negative/positive and categorical scores for aromatase (κ=0.41-0.67) and HER2 (κ =0.53-0.72). Many other studies [51][52][53][54] also report using Lucia software for their study.…”
Section: Special Purpose Softwarementioning
confidence: 99%